Vegetative Propagation of Acacia albida : a Promising Species for Farm-forestry in Arid Areas - Ahmed, Parvez (Indian Forester, 1987)
Acacia albida has been found very successful in the arid areas of Haryana. The plantation was started with few seeds provided by Forest Research Institute, Dehra Dun. The propagation of this species is a problem because the trees Of 10 years age in India did not set sufficient seed. It was succesfully raised from the shoot cuttings without any root hormone. The sprouted plants not only developed a healthy root system but also showed vigour and continuous growth after plantation. Its salient features and faster rate of growth gives the long waited solution to the problem of selection of species for the farm-forestry in arid areas.